IDENTIFIYING THE SUCCESSFULNESS OF A PROBLEM-BASED LEARNING IN AN UNDERGRADUATE MEDICAL EDUCATION PROGRAMME - Luh Ayu Viarini Dewi; Nancy M Rehatta; Budi Utomo (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Problem Based Learning (PBL) is active learning with a student-centered approach where unstructured issues are used as starting points for inquiry and learning process and problem-based learning is one of the teaching uses stimulus materials in helping the college students figure out the problems, questions, or issues. In a PBL system, the instructor helps the students develop problem solving skills, self-directed learning, so students can identify what they need to know how to know and how to access new information they need.Method: A cross-sectional study, using questionnaire distributed to 2015th generation of medical students in medical faculty of Airlangga University.Results: Result of data settlement, got 2 ways that is subjective and objective way, by using questioner by student, and objective using result of graduation of the course. From the results of the study, the results of the study program are prepared from students who are directly graduated from the problem-based learning program.Conclusion: This problem-based learning program is more successful than not using problem-based learning.